CONFLICTS IN THE ORGANIZATION AND METHODS OF THEIR RESOLUTION - Кравчук, Юлия; Шутяк, Ирина (SWorldJournal, 2021)
The paper focuses on the concept of organizational conflict. It also gives the analysis of different types of conflicts and methods of their resolution. On the basis of given methods the recommendations have been proposed for the resolution of conflicts